THE ROLE OF THE FAMILY IN INSTILLING CHARACTER EDUCATION VALUES IN YOUNG CHILDREN: HONESTY, DISCIPLINE, RESPONSIBILITY, AND POLITENESS - Agus Rifai; Nur Aisyah Zulkifli (STKIP Subang, 2025)
The application of character values in early childhood is widely regarded as a deliberate and systematic effort to nurture a generation of individuals characterized by virtue and moral integrity. The family, as the first and primary environment, plays a fundamental role in the process of internalizing character values through habituation, role modeling, and positive interactions. This study aims to analyze the role of the family in instilling four core character values namely honesty, discipline, responsibility, and politeness which are considered crucial for the moral development of early childhood. This study uses a descriptive qualitative approach, supported by a systematic literature review. The data presented in this study were obtained from various sources, including books, scientific articles, and regulations related to character education. The results show that the family has a dominant influence in shaping character through parenting, interpersonal communication, behavior regulation, and role modeling. This study makes a significant contribution to the field of family strategies in strengthening the character of early childhood amid the challenges of the digital age. It is hoped that these findings can serve as a reference for educators, parents, and future researchers in formulating family-based character building programs.